Effect of Seed Pretreatment and Site Preparation on the Success of Growing Acacia crasicarpa by Direct Seeding - NFN Nurhasybi; Dede J. Sudrajat (Jurnal Perbenihan Tanaman Hutan, 2020)
Critical land, which is still very large requires alternative reforestation methods, one of which is direct seeding. This study aims to determine the seed treatment and land preparation in direct seeding of A. crassicarpa seeds. The research was conducted in Parungpanjang, Bogor with a three-factor factorial randomized design, i.e. environmental conditions (A1=under the stand, A2=open area), seed treatment (B1=untreated, B2=soaked in hot water and allowed to cool for 24 hours), and sowing technique (C1=sowing on the soil surface without cleaning, C2=sowing on the soil surface of the cleared and loosened land, C3=sowing with 2-3 cm immerses on the cleared and loosened land). The results showed that seedlings under the stand tended to have better height growth (14.8 cm) compared to seedlings in open area (11.2 cm), as well as for seedlings diameter (under the stand 0.14 cm; in open area 0.11 cm). The application of the direct seeding of A. crassicarpa can be done by treating the seeds soaked in hot water allowed to cool for 24 hours and sowing methods by loosening the soil and immersing the seed 2-3 cm which results in 11% seedling survival, 11.85 cm height, and diameter 0.12 cm at 14 weeks after sowing.